The use of mesotherapy in sports medicine - Montalvan, B.; Parier, J.; Laurens, D. (Medicine and Science in Tennis, 2003)
About the Mesotherapie and its use in sportsmedicine. Mesotherapy involves a local injection of medication into the mesoderm, as close to the site of injury as possible. It is used primarily for its analgesic, anti-inflammatory and muscle-relaxing effects. In sports medicine, it can be of benefit to players with soft tissue injuries, who naturally aim to be able to return to play at the earliest opportunity.